Structural analysis of modern empires in the framework of global governance theory - Zaporozhchenko, R.; Запорожченко, Р.О. (ХНУ ім. В.Н. Каразіна, кафедра політології, 2016)
This present paper analyzes three powerful players of the modern global governance: the United States, the Russian Federation and the People's Republic of China. The main parameters that allow us to call them modern empires and help identify patterns of spreading influence are determined. The basic directions of geopolitical «giants» are used for comparative analysis of the imperial system of the above-mentioned countries.
Аналізуються три потужних гравців сучасного глобального управління: Сполучені Штати Америки, Російська Федерація та Китайська Народна Республіка. Визначаються основні параметри, які дозволяють назвати їх сучасними імперіями і допомагають виявити закономірності поширення впливу. Описані основні напрями геополітичних «гігантів» використовуються для порівняльного аналізу імперської системи перелічених країн.
Keywords: global governance; empire; geopolitics; globalization; imperial power; power; postempire; political sciense; глобальне управління; глобалізація; імперська влада; імперія